Swinger's Paradise Golf Range Sdn. Bhd. / Husnul Anwar Abd Wahab ... [et al.] - Abd Wahab, Husnul Anwar; Mohd Isa, Roshaidi; Jamaludin, Muhamad Nazrol; Abu Bakar, Sheith Faikis; Abd Nasir, Norazlina (Faculty of Communication and Media Studies, 2003)
Swinger's Paradise Golf Range Sdn Bhd is a company that provide services and facilities to customers / golfers to practice their swings. This company was form on 25 January 2003 and situated in Shah Alam. The company's aim is to be the premier golf range spot for the city and also to prove that Bumiputera can succeed in this form of business as today we can see there a lack young Bumiputera involve in business. So we take this challenge to open such business hoping it will set an example to other young Bumiputera entrepreneur to come out with such business.